Chromium-catalyzed para-selective formation of quaternary carbon centers by alkylation of benzamide derivatives - Pei Liu (Nature Portfolio, 2018)
The selective installation of quaternary carbon substituents on arenes is a highly challenging synthetic goal. Here, the authors report a chromium-catalyzed para-selective functionalization of benzamides with tertiary organometallic reagents under mild conditions.